Sugar and organic acids content in feijoa (Acca sellowiana) fruits, grown at two altitudes - Alfonso Parra-Coronado; Gerhard Fischer; Helber Enrique Balaguera-López; Luz Marina Melgarejo (Revista de Ciencias Agrícolas, 2022)
The impact of altitude on the different sugars and acids of the feijoa fruit is unknown. For that reason, the objective of this study was to evaluate the altitudinal effect on the content of organic acids (citric and malic) and sugars (glucose, fructose, and sucrose) during the development of feijoa fruits. The study took place in the towns of Tenjo (2,580 m asl with 12.3°C, 76.4% RH, 190mm precipitation) and San Francisco de Sales (1,800 m asl, with 18.5°C; 86.1% RH, 573 mm precipitation), located in Cundinamarca (Colombia). In the first locality (Tenjo), the fruits developed with 1,979 growth degree days (GDD) (180 days after anthesis (daa), while in the second locality (San Francisco), 2,728 GDD were required (155 daa). For organic acids, the predominant acid was citric. During the fruit development, the contents of these acids presented low values with a later irregular behavior, finally showing 14.21mg g-1 FW (fresh weight) at harvest for citric acid at San Francisco and 7.95mg g-1 FW at Tenjo. For malic acid, 9.14mg g-1 FW was recorded in San Francisco, and 6.88mg g-1 FW in Tenjo, with significant differences for citric acid between altitudes. The monosaccharides fructose and glucose increased during fruit development. However, the disaccharide sucrose showed a significant much higher content at 2,580 m asl (4.27mg g-1 FW) than at 1,800 m asl (1.03mg g-1 FW), for which it is concluded that the higher temperature in the low locality originated greater respiration and loss of sucrose in the fruit.